Keanekaragamaan dan Pemanfaatan Tumbuhan Obat Tradisional Pada Masyarakat di Kelurahan Lipu Kecamatan Betoambari Kota Baubau Provinsi Sulawesi Tenggara - Indrawati, Indrawati; Sabilu, Yusuf; Zainal, Puji Fitria (Jurnal BioWallacea, 2015)
The use of plants as traditional medicine has been known since long time ago bypeople in Lipu. This process has been inherited from one to next generation, nevertheless.nowdays, it has started to be extincted. So, it should be better to indentify the species ofplant used as traditional medicine by people in Lipu. The research aims to investigate thekinds of plant which uses as traditional medicine. The part of plant used and how to processand the adventage of the plant. The research used explorative survey method. The result ofthe research there are 54 species from 31 family of plants used as traditional medicine bythe people. The parts used of plant are leaf, stem/bark, root, flower, fruit, seed, tuber,rhizome and sap. The processing of the plants by refine, boil, squeeze, parch, pour boilingwater, rasp and without processing. And the ability of the plants are can treat kinds ofdisease.Keywords : Herbal medicine, Lipu Distric